Transformation and Evaporation of Surface Adsorbents on a Graphene "Hot Plate" - Choi, Jun Hee; Shin, Dong Hoon; Inani, Heena; Kwon, Min Hee; Mustonen, Kimmo; Mangler, Clemens; Park, Min; Jeong, Hyunjeong; Lee, Dong Su; Kotakoski, Jani; Lee, Sang Wook (American Chemical Society, 2020)
Dynamic surface modification of suspended graphene at high temperatures was directly observed with in situ scanning transmission electron microscopy (STEM) measurements. The suspended graphene devices were prepared on a SiN membrane substrate with a hole so that STEM observations could be conducted during Joule heating. Current-voltage characteristics of suspended graphene devices inside the STEM chamber were measured while monitoring and controlling the temperature of graphene by estimating the electrical power of the devices. During the in situ STEM observation at high temperatures, residual hydrocarbon adsorbents that had remained on graphene effectively evaporated creating large, atomically clean graphene areas. At other places, dynamic changes in the shape, position, and orientation of adsorbents could be directly observed. The temperature of the suspended graphene sample was estimated to reach up to 2000 K during the experiment, making graphene an efficient high-temperature micrometer-sized electron-transparent hot plate for future experiments in microscopes.
Keywords: TRANSPORT